Infected aneurysm of the thoracic aorta probably caused by Bacillus cereus: a case report - Tzu-Chi Wu; Ching-Chou Pai; Pin-Wen Huang; Chun-Bin Tung (BMC Infectious Diseases, 2019)
Abstract Background An infected aneurysm of the thoracic aorta is a rare clinical condition with significant morbidity and mortality. Patients with fast-growing aortic aneurysms show a high incidence of rupture. Gram-positive organisms, such as the Staphylococcus and Enterococcus species, are the most common cause of infection. Case presentation A 91-year-old man presented at our facility with high grade fever and tachypnea, which he had experienced for the previous two days. He had a history of end-stage renal disease and had been undergoing regular chest computed tomography (CT) follow-up for a left lower lung nodule. CT imaging with intravenous contrast media showed a thoracic aortic aneurysm with hemothorax. Rupture of the aneurysm was suspected. CT imaging performed a year ago showed a normal aorta. Blood samples showed a Bacillus cereus infection. The patient was successfully treated for a mycotic aortic aneurysm secondary to Bacillus cereus bacteremia. Conclusions Here, we report a rare of an infected aneurysm of the thoracic aorta probably caused by Bacillus cereus. Although infected aneurysms have been described well before, an aneurysm infected with Bacillus cereus is rare. Bacillus cereus, a gram-positive spore-building bacterium, can produce biofilms, which attach to catheters. It has recently emerged as a new organism that can cause serious infection.